GAMBARAN FAKTOR RESIKO TERJADINYA HIPERTENSI - Lamangida, Sri Yuningsi; Masi, Gresty Natalia Maria; Renteng , Septriani (Universitas Sam Ratulangi, 2025)
Background: Hypertension is a cardiovascular disease and is the most prevalent health issue in society. It is often referred to as